2013
DOI: 10.1016/j.jhep.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling and hepatocarcinogenesis: Molecular targets for the development of innovative anticancer drugs

Abstract: Hepatocellular carcinoma (HCC) is one of the most common causes of cancer death worldwide. HCC can be cured by radical therapies if early diagnosis is done while the tumor has remained of small size. Unfortunately, diagnosis is commonly late when the tumor has grown and spread. Thus, palliative approaches are usually applied such as transarterial intrahepatic chemoembolization and sorafenib, an anti-angiogenic agent and MAP kinase inhibitor. This latter is the only targeted therapy that has shown significant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
222
1
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(239 citation statements)
references
References 127 publications
5
222
1
11
Order By: Relevance
“…The differential expression of GPC3 can be used to differentiate and diagnose lung squamous cell carcinoma and lung adenocarcinoma. Basic research has indicated that GPC3 regulates the proliferation, differentiation, adhesion, and migration of tumor cells by modulating the insulin-like growth factor and wingless/integrated signaling pathways (Avanesov et al, 2012;Sakane et al, 2012;Pez et al, 2013;Dwivedi et al, 2013;Avanesov and Blair, 2013), thus playing important roles in tumor growth and metastasis. Stronger GPC3 expression has been correlated with increased growth and metastatic potential (Tanaka et al, 2011;Gao and Ho, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The differential expression of GPC3 can be used to differentiate and diagnose lung squamous cell carcinoma and lung adenocarcinoma. Basic research has indicated that GPC3 regulates the proliferation, differentiation, adhesion, and migration of tumor cells by modulating the insulin-like growth factor and wingless/integrated signaling pathways (Avanesov et al, 2012;Sakane et al, 2012;Pez et al, 2013;Dwivedi et al, 2013;Avanesov and Blair, 2013), thus playing important roles in tumor growth and metastasis. Stronger GPC3 expression has been correlated with increased growth and metastatic potential (Tanaka et al, 2011;Gao and Ho, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the canonical and non-canonical Wnt pathway in liver oncogenesis has been described by various investigators [59][60][61][62][63][64][65][66][67]. One of the most frequently described mechanisms for activation of the canonical signaling pathway in HCC involves activation of β-catenin through mutations in the CTNNB1 gene.…”
Section: Disturbances In Wnt/β-catenin Pathway In Liver Carcinogenesismentioning
confidence: 99%
“…Interestingly, mutations in the β-catenin gene in hepatocellular carcinomas induce overexpression of β-catenin targets such as the glutamine synthetase gene GLUL (66,67), whereas hepatocytes from glutamine synthetase-negative tumours are often H-ras or BRAF mutated and express E-cadherin, reflecting perivenous and periportal profiles, respectively (68). Loss-of-function in APC and Axin is mutually exclusive to CTNNB1 mutations and has been detected in 1-3% and 8-15% of hepatocellular carcinoma cases (for review, see (69)). …”
Section: Wnt/β-catenin Signalling and Cancermentioning
confidence: 99%